Stress, Thyroid Hormone Secretion and Vestibular Stimulation: A Review of the Links - Kurien, Mukkadan Joseph; Rajagopalan, Archana; Sailesh, Kumar Sai; Varghese, Varsha; Amin, Arati; Reddy, Udaya Kumar; Kochakkan Varghese, Jinu; Mishra, Soumya (Biology, Engineering, Medicine and Science Reports)
Stress is part and parcel of our daily life. It is defined as a state of disharmony or threatened homeostasis. Stress can specifically influence several systems. Here we review the interactions of stress and thyroid hormone secretion and vestibular stimulation to suggest necessary translational research in this area. Vestibular stimulation may be used as a supplemental therapy for thyroid disorders. We suggest detailed studies in this area to explore importance of vestibular stimulation in the management of thyroid disorders.
Keywords: Stress; Vestibular stimulation; Translational Research; Thyroid secretion; Homeostasis